(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
The continuous increase in the shift of interest from synthetic drugs to medicinal plants source of drugs necessitates the screening of traditional plants (grown in Northeastern Nigeria) for their antioxidant potential, phytochemicals, and minerals content. This is an attempt to pave way for the scientific identification of plants with proven medicinal val ues. Therefore, the aim of this research was to determine the antioxidant potential, phy tochemicals, and minerals content of the root extract of Physalis angulata, which is a herb commonly found even along road sides in the rural areas of northeastern Nigeria. The anti oxidant potential, phytochemicals, and minerals content were determined using standard methods. The results of the qualitative phytochemical analysis revealed the presence of alkaloids, terpenoids, saponins, glycosides, and flavonoids. Quantitatively, the amount of the aforementioned phytochemicals was found to be 14.96% + 0.86% (alkaloids), 13.79% + 0.04% (terpenoids), 12.78% + 2.4% (saponins), 0.05% + 0.03% (glycosides), and 0.05% + 0.00% (flavonoids). The result of this research also showed that the extract contains magnesium (1,101.50 + 2.12 ppm), sodium (407.20 + 0.42 ppm), calcium (76.96 + 0.79 ppm), zinc (4.95 + 0.07 ppm), potassium (2.05 + 0.07 ppm), manganese (1.84 + 0.05 ppm), copper (1.10 + 0.14 ppm), cobalt (0.63 + 0.04 ppm), and selenium (0.20 + 0.01 ppm). The result of the in vitro antioxidant activity (AOA) of the terpenoid fraction showed that there was a dose-dependent increase in the AOA as the concentration of the terpenoid increased from 20 to 1,000 µg/ml. These results suggest that the extract may exert all the activities associated with the phytochemicals it contains; it may also serve as a source of minerals – which are essential for maintenance and perpetuation of life – found in it; and it may also serve as an antioxidant. However, it is suggested that in vivo experiments be conducted to test for the activities that the root extract is assumed to possess due to the phytoconstituents it contains (as revealed by this research).